Drimane sesquiterpenoids from a wetland soil-derived fungus Aspergillus calidoustus TJ403-EL05 - Sitian Zhang; Shuyuan Mo; Fengli Li; Yaxin Zhang; Jianping Wang; Zhengxi Hu; Yonghui Zhang (Natural Products and Bioprospecting, 2022)
Abstract Soil-derived fungi represent an insufficiently tapped reservoir for discovering new and bioactive natural products (NPs), and despite an ever-increasing number of unknown NPs have been discovered over the past few decades, much of the hidden biosynthetic potential is still in an urgent need to be disclosed. In this research, a chemical investigation was performed on a wetland soil-derived fungus Aspergillus calidoustus TJ403-EL05, leading to the isolation of a total of fourteen drimane sesquiterpenoids (1–14), incorporating three new ones, namely ustusols F–H (1–3). Their structures, comprising absolute configurations, were completely authenticated by widespread spectroscopic data, quantum chemical 13C NMR and ECD calculations, and X-ray crystallography experiments. Compound 14 exhibited moderate anti-inflammatory activity by inhibiting the LPS-induced NO release (IC50 = 25.6 μM). Graphical Abstract